A comparison of 5-year administration of cyproterone acetate or leuprolide acetate in combination with estradiol in transwomen. Issue 6 (December 2020) - Gava, Giulia; Mancini, Ilaria; Alvisi, Stefania; Seracchioli, Renato; Meriggiola, Maria Cristina
Abstract : Objective: The impact of different combinations of long-term gender-affirming hormone therapy (GAHT) in transwomen (TW) is largely unknown. To assess the effects of 5-year administration of cyproterone acetate (CPA) or leuprolide acetate (Leu) plus transdermal or oral estradiol (E). Design: Cohort study based on prospectively collected data. Fifty TW received 50 mg CPA daily orally ( n = 25; CPA+E group) or 3.75 mg Leu i.m. monthly ( n = 25; Leu+E group) with 1 or 2 mg E daily for 5 years. Reproductive hormones, biochemical and anthropometric parameters, body composition and bone mineral density (BMD) were assessed. Results: LH, FSH and total testosterone levels were similarly and significantly suppressed in both groups. Prolactin increased only in the CPA+E group ( P = 0.002). Fasting insulin resistance and glucose progressively increased in the CPA+E group only (treatment × time effect P = 0.002 and P = 0.043, respectively). Total cholesterol increased more in the Leu+E group than in the CPA+E group and HDL-cholesterol decreased in the CPA+E group (time × treatment interaction effect, P = 0.007). Lumbar and total body BMD increased in both groups after 3 years. No serious adverse events were recorded. Conclusions: Both regimens were effective in suppression of T production. CPA+E worsened the metabolic profile with a slight increase in PRL levels. All subjects presented an increase in BMD regardless of treatment. These preliminary data could have clinical implications in the choice of GAHT, in particular for those TW not requiring gender-affirming surgery.